Histo-morphologic Spectrum of Non-Hodgkin Lymphoma According to WHO Classification 2016: A Cross-Sectional Study - Yasmin, Shamoli; Haque, Wasim Selimul; Islam, SK Md Jaynul; Ahmed, Ishtyaq; Hossain, Sowkat; Saha, Debashish (BIRDEM Medical Journal, 2018)
Background: Geographic variations with regard to incidence and histological subtypes are known to occur in Non-Hodgkin lymphoma (NHL). This study was aimed to see the incidence and subtypes of NHL in a group of Bangladeshi population. Methods: This cross sectional study was carried out in Armed Forces Institute of Pathology (AFIP) Bangladesh, from 1st April 2017 to 31st March 2018. All nodal and extranodal tissues which were morphologically diagnosed as NHL were included in the study and immunohistochemistry was done for sub-classification according to WHO classification 2016. Bone marrow trephine biopsy samples were excluded. Results: Total cases: 106, mean age: 48.5 years ± 18.5 (range 2Y 9 M –82 years), male-female ratio: 2.2:1. Total subject of B cell Lymphoma (BNHL): 83 (78.3%) and T cell lymphoma (TNHL): 23 (21.7%). Among BNHL, total subjects of diffuse large B cell lymphoma (DLBCL) 50 (60%), follicular lymphoma 9 (11%), marginal zone lymphoma 8 (10%), small cell lymphoma and mantle cell lymphoma 5 (6%) each, Burkitt lymphoma 4 (5%) and B cell lymphoblastic lymphoma 2 (1.89%) in number. Among TNHL peripheral T-cell lymphoma NOS 11 (48%), anaplastic large cell lymphoma (ALCL) 5 (22%), T cell lymphoblastic lymphoma 4 (17%), and angio-immunoblastic T cell lymphoma 3 (13%) in number. Among 5 ALCL, 4 ALK positive and 1 ALK negative. Number of primary extra-nodal NHL were 29 (27%) with most common involved organ system being GIT and most common histological subtype being DLBCL. Conclusion: Quite similar pattern of age range with mean age, male to female ratio, subtypes and extra nodal NHL distribution prevailing in our subcontinent is found in our population with subtle increased incidence of TNHL indicating the necessity of further large epidemiological study. Birdem Med J 2018; 8(3): 215-222